STRATEGI PEMERINTAH KOTA PARIAMAN DALAM PENGEMBANGAN SENTRA INDUSTRI KECIL MENENGAH - Jumadil Anshari; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
Abstract This study aims to determine the strategy of the City Government in the Development of Small and Medium Industry Centers Case Study in Kampung Perak, Kota Pariaman. This research was carried out because it saw the trading activities of the silver village which were still underdeveloped and were lacking in marketing and human resources. This research is a qualitative research with a descriptive approach. The informants selected in this study used purposive sampling and incidental sampling techniques. Data collection techniques with observation, documentation, and in-depth interviews. As well as data validity testing using source triangulation and method triangulation. Based on the results of this study indicate that in Based on the results of this study indicate that in the strategy of the City Government in the Development of Small and Medium Industry Centers Case Study in Kampung Perak, Kota Pariaman which is still undeveloped due to the lack of knowledge of traders in the silver village in the field of marketing and human Resources . Keywords: Strategy, Development, UMKM, Kampung Perak Ringan